Fermi-LAT detection of G118.4+37.0: a supernova remnant in the Galactic halo seen around the Calvera pulsar - Araya Arguedas, Miguel (2023)
The discovery of a non-thermal radio ring of low surface brightness about one degree in diameter has been recently reported around the location in the sky of the Calvera pulsar, at a high Galactic latitude. The radio properties point to it likely being a new supernova remnant (SNR), G118.4+37.0. We report an analysis of almost 14 yr of observations of this region by the γ-ray Large Area Telescope onboard the Fermi satellite. We detect extended GeV emission consistent with the size and location of the radio source, which confirms the presence of relativistic particles. The spectrum of the high-energy emission is fully compatible with an origin in the same relativistic particles producing the radio emission. These features and its similarities to other isolated SNRs establish this source as the remnant of a supernova. A simple model of the non-thermal emission from radio to GeV energies resulting from leptonic emission from electrons produced by the SNR is presented. G118.4+37.0 and other similar isolated remnants could be part of a radio-dim SNR population evolving in low density environments showing hard GeV emission of leptonic origin. Future deeper surveys in radio and γ-rays could discover new members of the group.